Comparing perceptions of student teachers and regular education teachers toward students who stutter: a mixed-method approach. (2nd October 2018) - Panico, James; Daniels, Derek E.; Hughes, Stephanie; Smith, Randall E.; Zelenak, Jennie
ABSTRACT: Purpose: A mixed-methods approach was used to explore the perceptions of student teachers and regular education teachers toward students who stutter. Method: A total of 224 participants (107 regular education teachers and 117 student teachers) completed an anonymous survey that asked about general knowledge of stuttering, perceptions toward students who stutter, and beliefs about classroom participation and accommodations for students who stutter. Results: Quantitative analyses revealed few significant differences between groups. Additionally, a qualitative thematic analysis uncovered four major themes that consisted of (1) knowledge of and exposure to stuttering, (2) comfort level, (3) classroom accommodations, and (4) instructor support. Conclusion: Overall, results from the study indicated that student teachers and regular education teachers need increased knowledge about stuttering as well as information regarding how to best accommodate students who stutter in the classroom. Limitations and future research are also discussed.